Role of Village Government in Waste Management in Kejapanan Village, Gempol District, Pasuruan Regency: Peran Pemerintah Desa dalam Pengelolaan Sampah di Desa Kejapanan Kecamatan Gempol Kabupaten Pasuruan - Tadasi, An Nisa'Reigi; Choiriyah, Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2023)
This qualitative descriptive study investigates waste management in Kejapanan Village, Gempol District, Pasuruan Regency, focusing on the government's role and influencing factors. Employing interviews, observation, and documentation, the research reveals the government's dual role as motivator and facilitator through community empowerment, training, and providing essential facilities. Collaborations with environmental services address staffing shortages. Supporting factors include community appreciation and cooperation, while hindrances involve damaged garbage trucks and insufficient waste management machinery. The implications underscore the need for repairs, additions, and improved collaboration to enhance waste management in Kejapanan Village, offering insights applicable to global waste management challenges Highlight : The study explores the multifaceted role of the government in waste management, emphasizing its function as a motivator and facilitator through community empowerment initiatives. Significant aspects include the provision of essential facilities by the village government, such as warehouses, toilets, and waste-handling machinery, contributing to effective waste management programs. Collaboration with environmental services is identified as a crucial dynamic, addressing staffing shortages and highlighting the importance of inter-agency cooperation for comprehensive waste management solutions Keywords: Waste Management, Government Role, Community Empowerment, Environmental Collaboration, Infrastructure Improvement